(untitled) (Baghdad Science Journal, 2024)
Coleus amboinicus Lour. is a herbal plant with immunoregulatory effects due to the polyphenols it contains. This research aims to determine the effects of Coleus amboinicus Lour. leaf extract on the biochemical markers and the liver histopathological scores of septic rat model. We used 28 Rattus norvegicus rats for the study and divided them into 4 groups consisting of 7 rats each: control (healthy rats without treatment), group 1 (septic rats treated with antibiotics), group 2 (septic rats treated with antibiotics and 250 mg/kg body weight of Coleus amboinicus Lour. leaf extract), and group 3 (septic rats treated with antibiotics and 500 mg/kg body weight of Coleus amboinicus Lour. leaf extract). We measured the serum glucose, aspartate aminotransferase (AST), alanine aminotransferase (ALT), urea, and creatinine levels, as well as the liver histopathological scores, to assess the improvement. Results showed a decrease in the serum glucose, AST, ALT, urea, and creatinine levels of the rat groups given Coleus amboinicus Lour. leaf extract compared to the rat group given only antibiotics, though the decrease was not significant (p = 0.393; p = 0.064; p = 0.961; p = 0.288; p = 0.119, respectively). However, there was a significant decrease in the liver histopathological scores of the rat groups given Coleus amboinicus Lour. leaf extract compared to the rat group given only antibiotics (p = 0.003). To conclude, Coleus amboinicus Lour. leaf extract administration has no significant effect on the biochemical markers but improves the liver histopathological scores in septic rat model.